Assessment of the Finlay Journal Scientific Production According to the Web of Science - Alex Véliz Burgos; Carolina Cabezas Cáceres; Belkis González Aguiar; Alain Francisco Morejón Giraldoni; Anita Dörner Paris (Universidad de las Ciencias Médicas de Cienfuegos, 2018)
Foundation: bibliometry allows to analize the scientific production of a country, institution or particular author. The best journals worldwide do bibliometric studies to determine if they are competitive with their pairs in a thematic knowledge area. Objective: to evaluate the scientific production of the Finlay Journal in the period 2015-2017. Method: a bibliometric study was realized in which he production analyzed is done during the years 2015 to 2017, the information was extracted up to January 7th 2018, data base from the Web of Science was used. The 144 articles examined were imported to a data base elaborated, with this purpose, using Excel Microsoft. The variables considered were: year of the publication, author's production, institutions, countries, topics, languages, average quotes per publication and number of authors per article. In addition indicators h, g and e were used. The results were presented in tables in order to be able to evaluate the scientific production of the journal. Results: topics related with internal medicine predominated, the most productive author was Miguel Serra Valdés, also the most prolific institution was the Gustavo Aldereguía Lima University Hospital, Cuba is the country with the highest contribution of articles. Conclusion: the Finlay Journal has progressively been consolidating its quality and impact in the competitive environment within the Web of Science.